Successful transitions from public to private-sector led growth - Diallo, Aissatou (International Monetary Fund, 2021)
Many Sub-Saharan African (SSA) countries, like Benin, have scaled up public investment during the last decade. Such a strategy contributed to the improvement of infrastructure, but also to a build-up of debt vulnerabilities. Looking forward, the planned fiscal consolidation will result in some restraint of public spending, and, in particular, public investment. In this context, maintaining or even raising the region's economic growth will require an offset by the private sector. The analysis draws lessons from countries that have successfully transitioned from public investment to private investment-led growth using a global sample starting in the mid-1980s. These lessons highlight policies that have been crucial in fostering a rebound of private investment in the wake of a contraction of public investment. The analytical framework proposed by Hausman, Rodrik and Velasco (2005) is used to identify and classify such policies. Finally, the paper analyses how the identified policies could help Benin achieving a smooth transition from public to private sector-led growth
10.5089/9781589068544.001
Keywords: Graue Literatur; Private and public investment; growth; transition; lessons; Growth; Transition; Fiscal Consolidation and Lessons; Macroeconomic Aspects of International Trade and Finance; Macroeconomic Policy; Macroeconomic Aspects of Public Finance; and General Outlook; Money and Interest Rates; Private and Public Investment; fiscal consolidation; Investments: General; Public Finance; Macroeconomics: Consumption; Saving; Production; Employment; and Investment: General (includes Measurement and Data); Money and Interest Rates: General; Macroeconomic Policy; Macroeconomic Aspects of Public Finance; and General Outlook: General; Macroeconomic Aspects of International Trade and Finance: General; Taxation; Subsidies; and Revenue: General; Fiscal Policies and Behavior of Economic Agents: General; National Government Expenditures and Related Policies: General; National Budget; Deficit; and Debt: General; Investment; Capital; Intangible Capital; Capacity; National Government Expenditures and Related Policies: Infrastructures; Other Public Investment and Capital Stock; Fiscal Policy; Debt; Debt Management; Sovereign Debt; Economic & financial crises & disasters; Economics of specific sectors; Economics: General; Public finance & taxation; Private investment; National accounts; Public investment spending; Expenditure; Macroeconomics; Infrastructure; Public debt; Currency crises; Informal sector; Economics; Saving and investment; Public investments; Fiscal policy; Debts; Public